Essays on the emerging market platform's performance and internationalization - Li, Yang (Nanyang Technological University, 2021)
The rise of digital platforms has brought great changes to the modern business environment. The presence of network effects and the unique technical architecture make platforms different from traditional firms in the strategies to achieve market dominance and international expansion. Although the emergence of platforms has attracted significant attention from scholars across various disciplines, existing platform studies provide little insight into the platforms that originated from emerging markets. Since recent years have witnessed the rapid development and international expansion of the emerging market platforms, it is necessary to investigate the factors that influence the development and internationalization of emerging market platforms to provide a more complete picture for platform studies. Therefore, this dissertation focuses on the platforms from emerging markets and studies the factors that influence the market dominance and international expansion of emerging market platforms. Essay 1 explores the validity of Winner-Take-All (WTA) hypothesis and the underlying mechanisms that condition the relationship between the installed base of a platform and the platform’s performance in the context of emerging markets. I propose a positive relationship between the existing user base of a platform and the focal platform’s performance and explore the moderating effects of two boundary conditions: existing users’ evaluation ambiguity and economic policy uncertainty. By utilizing a longitudinal sample of Chinese peer to peer lending (P2P) platforms from 2017 to 2019, I confirm the positive relationship between the installed base of a platform and the platform’s performance, however, the positive relationship will be weakened when the existing users provide ambiguous evaluation information and will be strengthened when the level of economic policy uncertainty is high in the external environment. Drawing on the diffusion of innovation theory, Essay 2 posits that the development of communication channels in the host countries contributes to the platforms’ international penetration. I focus on the cultural distance between the home and host country of the platform and the user-defined advantage of the platform to assess the boundary conditions of the relationship. I empirically test the hypothesis utilizing the archival data of Chinese listed platforms from 2013 to 2019. The results confirm that the social media penetration rate positively influences the platform’s penetration in the host country. Such influence is weakened by the cultural distance between the home and the host country of the platform and strengthened by the host country's existing users’ positive evaluation information. The study contributes to the existing understanding of the internationalization of digital platforms. Essay 3 focuses on the role of platform-specific advantages, such as network value and product value on the platform's international penetration. I focus on the host country’s characteristics to assess the boundary conditions of the relationship between these platform-specific advantages and the success of the platform's international penetration. The empirical testing utilizes the archival data of Chinese social media platforms for 2016-2020. The results show that both network value and product value positively influence the success of a platform’s international penetration. The host country’s market dominance will weaken the relationship between the network value and the platform’s penetration while the digitalization distance between the host and the home country will strengthen the relationship between the product value and the platform’s penetration. The study provides valuable insights for theory and practice in the internationalization of digital platforms.